Qibla Direction Accuracy in Bangka Belitung Mosques: An Astronomical–Geospatial Study - Reno Ismanto; Ahmad Fadholi; Priyanggo Karunia Rahman; Ahmad Zulpan (Fakultas Syari'ah dan Hukum UIN Walisongo, 2026)
Accurate Qibla orientation is essential for the validity of Muslim prayer; inconsistencies in both traditional and modern determination methods continue to produce significant inaccuracies, particularly in archipelagic regions. This study assesses the accuracy of Qibla direction in mosques across the Bangka Belitung Islands, Indonesia, and evaluates the methods used to determine it. A mixed-methods approach was employed, combining field measurements of 70 mosques using the solar shadow (istiwā’ainī) method and GPS-based applications with semi-structured interviews. Measured orientations were compared with geodetically calculated azimuths, and spatial distribution patterns were analyzed using Geographic Information Systems (GIS). The results show that only 30% of mosques are accurately aligned (≤2° deviation), while 54% are less accurate and 16% are significantly misaligned (>10°). GIS-based analysis reveals spatial variability in deviation patterns, indicating unequal access to technical knowledge and measurement tools. This study contributes to integrating astronomical, geodetic, and geospatial approaches for Qibla determination and highlights the need for standardized verification practices in geographically fragmented regions.